Capturing stakeholder perceptions of graduate capability development: Challenges associated with Graduate Employability Indicators - Whelan, Barbara; Oliver, Beverley; Hunt, L.; Hammer, S.; Jones, S.; Pearce, A. (Australian Collaborative Educational Network, 2010)
This paper reports on the use of the Graduate Employability Indicators, a suite of three online surveys for graduates, employers and members of the course teaching team, developed through the ALTC Project Building Course Team Capacity for Graduate Employability. The surveys were administered to graduates, employers and faculty staff for accounting and public relations/communications courses at four Australian universities in early 2010. Strategies used to identify and engage employers are discussed along with the impact that these strategies had on the total responses. Factors the ALTC Project Team found important were identifying and collating employer contacts, sending out reminder emails and establishing personal contact with stakeholders wherever possible. The paper also presents the lessons learnt through this survey process that may apply to activities undertaken by other researchers.